Advances in research on the role of gut microbiota in the pathogenesis and precision management of gallstone disease - Tan, Ludong; Jia, Feng; Liu, Yahui (Frontiers in Medicine, 2025)
Gallstone disease remains a prevalent global gastrointestinal condition with a rising incidence, posing substantial challenges to healthcare systems and public health initiatives. Advances in multi-omics and sequencing technologies have illuminated the pivotal role of gut microbiota in its pathogenesis, progression, and management. This article reviews the disrupted microbiota profiles observed in patients with gallstone disease and their connection to the metabolic pathways involved in gallstone formation, particularly focusing on cholesterol metabolism, bile acid dynamics, and inflammatory pathways. It also discusses the enduring impacts of cholecystectomy on gut microbial functions and their metabolic implications. Novel strategies targeting gut microbiota, including probiotics, microbial metabolite supplementation, dietary adjustments, integrative medicine, and emerging microbial therapies, present promising avenues for precise treatment. Furthermore, this review underscores the value of future research into multi-omics integration, microbiome engineering, and global collaborations, advocating for interdisciplinary and personalized approaches to gallstone management. However, unresolved challenges, such as ensuring stable colonization of functional microbiota, refining tailored therapeutic strategies, and assessing long-term outcomes, warrant further investigation. This work aims to provide a comprehensive resource for understanding gallstone disease within a microecological framework, supporting the development of precision medicine-based prevention and treatment paradigms.